A study satisfaction about quality of taxi service in Kota Bharu, Kelantan - Raja Norhayati, Raja Sulaiman (2015)
The Transportation is plays an important role in the life of human society since time immemorial for a living, transporting goods and also for the purpose of living, as well as to the movement of people from one destination to another. In developed countries, taxis tend to be used as a substitute for private vehicles by passengers who use the service for convenience reasons or because they do not want to own a car, even though they can afford it. The customer satisfaction on taxi services in Kota Bharu to determine level of customer satisfaction in term of fare, comfortable, taxi driver and convenience. The literature review refers to consider the taxicab as part of a larger urban transportation system, typically emphasizing the taxicabs optimal role within that system and within cities. In a comprehensive historical review of the taxicab industry, Gilbert and Samuels (1982) cite conventional transits inability to provide satisfactory mobility to certain urban areas in a cost-effective manner, and see taxicabs as one solution to that problem. Their books historical account examines the taxicabs role through this lens, supporting the argument that public transit programs and subsidies should incorporate taxicabs. The study was performed using questionnaire of the passengers that ride taxi in study area. This questionnaire will be given to all respondents regardless of whether the student, employee, and non-student-employee. This studies of passenger are satisfied with seating, conditions outside and inside of taxi, information (schedule), smell, driver style and driver friendly and so on. The results obtained from the respondents about level of dissatisfaction on quality of taxi service such as taxi fare, comfortable, taxi driver and convenience. At the end of this study found that the level of customer satisfaction such as fares, comfortable, and convenience, of taxi services are still not satisfactory. The suggestion have made based from this study with establish of meter system, renew all the taxis, to improve all the comfortable on taxi service and others.